Granular cell tumour of the bronchus: bronchoscopic and clinical features. Issue 12 (December 1986) - Hernandez, O G; Haponik, E F; Summer, W R
Abstract : Granular cell tumours are uncommon, generally benign neoplasms of uncertain origin that occasionally affect the tracheobronchial tree. Their incidence seems to be increasing, despite the fact that such tumours are rarely suspected on clinical grounds or bronchoscopic appearance. Here we describe three cases of endobronchial granular cell tumours, one of which regressed spontaneously after biopsy, and review previous accounts of their bronchoscopic and clinical features.